THE IMPORTANCE OF CONSISTENT TERMINOLOGY IN TECHNICAL TRANSLATION - Axunbabaeva Nargiza Xamidjanovna (Galaxy International Interdisciplinary Research Journal, 2023)
Technical translation is a type of specialized translation involving the translation of documents produced by technical writers (owner’s manuals, user guides, etc.), or more specifically, texts which relate to technological subject areas or texts which deal with the practical application of scientific and technological information. While the presence of specialized terminology is a feature of technical texts, specialized terminology alone is not sufficient for classifying a text as "technical" since numerous disciplines and subjects which are not "technical" possess what can be regarded as specialized terminology. Technical translation covers the translation of many kinds of specialized texts and requires a high level of subject knowledge and mastery of the relevant terminology and writing conventions. As technology creates easier and faster means of communication and the world moves toward becoming a global community, the need to communicate with people from multiple language backgrounds also grows. Technical Translation Requires Specific Skills. Technical translation is an area that needs specialization to ensure that the correct technical flow is in place. This specific type of language service is never easy, despite appearing to be direct or even literal. The nature of the texts to be translated often requires an above-average understanding of the topic. For example, general translators wouldn’t necessarily know the correct terms to describe electrical or mechanical items regardless of their language skills.